PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN DI SERUNI COFFEE BALIKPAPAN - Febrianti, Santi; Sukimin, Sukimin; Indriastuty, Nina (Fakultas Ekonomi Universitas Balikpapan, 2024)
This research aims to analyze the partial and simultaneous influence of marketing mix variables (product, price, place, promotion, people, physical evidence, and process) on purchasing decisions at Seruni Coffee Balikpapan. The type of research used is quantitative research. The number of samples in this research was 373 consumers who made purchase transactions at Seruni Coffee Balikpapan. The sampling technique used in this research is non-probability sampling with accidental sampling. The data analysis used is descriptive analysis and multiple linear regression analysis. The test tools used are instrument testing, classical assumption testing, and hypothesis testing. The results of multiple linear regression analysis show that product, price, place, promotion, people, physical evidence and process variables have a positive and significant influence on purchasing decisions, either partially or simultaneously. Product variables have the most dominant influence on purchasing decisions at Seruni Coffee Balikpapan.